Kebijakan Desentralisasi dan Disparitas Pendidikan Lokal di Provinsi Sulawesi Tenggara - Obed Bida (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2021)
Paradoxically, decentralization policies can increase the participation and effectiveness of education services, but in the context of public policies, it can also lead to educational disparities in society. This research was conducted to explain educational disparities in the perspective of decentralization policies as part of a public problem. This research method uses an interactive qualitative approach with data collection techniques through observation, a document study, and in-depth interviews and is analyzed using Spradley data analysis. The results showed that education policies in the regions did not create a balance, but instead opened up space for educational disparities in society, through the spatial and structural approach policy patterns. The dynamics of the education policy process are reflected in the contestation of the structural and political elites which tend to interfere with the efficiency, effectiveness, and professionalism of education management. Local governments are often trapped in political interests and always place